DAMPAK FEAR OF MISSING OUT (FOMO) TERHADAP PERILAKU KONSUMTIF DAN IMPULSIF GENERASI Z DI ERA DIGITAL - Nazita Oktia Putri; Putri Maharani; Adrias; Nur Azmi Alwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the impact of Fear of Missing Out (FoMO) on the consumptive and impulsive behavior of Generation Z in the digital era, particularly in online shopping activities influenced by social media and e-commerce platforms. Data were collected through a Google Form questionnaire distributed to 33 Generation Z respondents aged 19–23 years who actively use social media every day, using a purposive sampling technique. The results show that FoMO has a fairly strong influence on consumptive and impulsive behavior, where most respondents admitted to making purchases because they saw viral products, were attracted by promotions and discounts, and were driven by the fear of missing current trends. In addition, social media also triggers higher levels of social comparison behavior, increased spending, and feelings of regret after purchasing items that do not meet expectations or are rarely used. In conclusion, social media is the main factor that strengthens consumptive and impulsive behavior among Generation Z, so digital literacy and self-control are needed in social media use and online shopping activities.